Modern approaches to the therapy of computer visual syndrome - Zakharova M.A.; Zh.G. Oganezova (РМЖ "Клиническая офтальмология")
Zakharova M.A.1, Oganezova J.G.2 1 S. Fyodorov Eye Microsurgery Federal State Institution, Moscow 2 Pirogov Russian National Research Medical University, Moscow In the modern world, computers and electronic devices have become universal tools that are actively used not only in professional activities, but during the rest. However, doctors noted the growth of  pathological changes in the organs and systems of the human body, induced by work at the computer. It is computer syndrome, which includes changes in the skeleto-muscular system, carpal tunnel syndrome and computer vision syndrome (CVS). According to the estimates of different researchers, working with a computer for more than three hours a day leads to the development of the CVS in its different manifestations in 64-90% of users. At the same time, the risk of developing a CVS increases with increasing duration of work at the computer. Long-term work behind the computer monitor can be considered as a stress regime for the organ of vision, which is accompanied by a disturbance of the oxidation-antioxidant balance with the formation of free radicals that contribute to the damage of biological membranes, causing tissue hypoxia and the release of inflammatory mediators. Therefore, CVS treatment should be comprehensive and include traditional methods of treatment and use of anthocyanozides. This article discusses an integrated approach to treatment of the CVS, it focuses on the effectiveness of drugs containing anthocyanozides.  Key words: computer vision syndrome, anthocyanozides, bilberry extract, complex treatment of computer visual syndrome. For citation: Zakharova M.A., Oganezova J.G. Modern approaches to the therapy of computer visual syndrome // RMJ “Clinical ophthalmology”. 2018;1:50–54.